Fe (Ferro) Analysis of Iron Sand for Iron Pellet - Juhana, Riyadi (Rekayasa Material, Manufaktur dan Energi, 2025)
Iron sand is the main ingredient of making iron pellets. Iron pellets are the main ingredient of steel plates. Iron pellets for steel industry in Indonesia are still imported from Sweden, Brazil, and Chille.  The reason for import that Ferro content in the local production of iron pellets is less than 60% (Fe 60%).  The effect that Ferro (Fe) quality in the local iron sand as the main ingredient of iron pellets is assumed to be less than 60%. This issue should prove that the assumption is incorrect. The research aims to prove that the level of Ferro contained in the local iron sand is more than or equal to 60%. The research also proves that local iron sand can be finished with quality iron pellets. The results showed that Ferro levels contained in local iron sand ranged from 71.03% to 73.05%, compared to Ferro levels outside of iron sand ranging from 61.00% to 68.90%. Based on the results of a comparison of Ferro rates on iron sand, Ferro content on local iron sand is greater than the iron sand content of Ferro abroad. Then it can be concluded that the level of Ferro in local iron sand is less than 60% is not proven, hence the reason steel industry uses imported iron pellets with the reason of Fe level local iron sand is less than 60%, not based on the results of scientific research.